Artificial Intelligence in Islamic Educational Management: An Integrative Ethical Framework for Society 5.0 - Amrina Rosyada Al Hadi; Muslim Muslim; Dwi Khoirmiah; Idi Warsah; Irwan Fathurrochman; Eka Apriani (Academicus: Journal of Teaching and Learning, 2026)
Artificial Intelligence (AI) has become an important driver of educational transformation in the Society 5.0 era. While previous studies have focused largely on teaching and learning, the role of AI in Islamic educational management remains relatively underexplored. In addition, few studies have integrated educational management, the human-centered orientation of Society 5.0, and Islamic ethical values within a single framework. This study examines the utilization of AI in Islamic educational management, explores its benefits and risks, and proposes an integrative model grounded in Islamic ethics. Using an integrative literature review and thematic content analysis, data were collected from academic databases, scholarly books, policy documents, and authoritative reports. The findings indicate that AI can support planning, organizing, actuating, and controlling/evaluating functions through academic data management, integrated information systems, digital services, personalized learning, and data-informed decision-making. However, challenges remain, including academic plagiarism, algorithmic bias, data privacy concerns, technological dependence, and unequal access. To address these issues, this study proposes the Islamic AI-Based Educational Management Framework, consisting of five components: Input, Process, Ethical Filter, Output, and Impact. The framework integrates educational management, Society 5.0 principles, and Islamic ethical values to support AI implementation that remains effective, ethical, human-centered, and aligned with the broader goals of Islamic education.